Effects of Brazilian green propolis on double‐stranded RNA‐mediated induction of interferon‐inducible gene and inhibition of recruitment of polymorphonuclear cells. (26th September 2012) - Hayakari, Ryo; Matsumiya, Tomoh; Xing, Fei; Tayone, Janeth C; Dempoya, Junichi; Tatsuta, Tetsuya; Aizawa‐Yashiro, Tomomi; Imaizumi, Tadaatsu; Yoshida, Hidemi; Satoh, Kei
Abstract Background Propolis is a bee product with various biological properties, including an antiviral activity when taken orally. However, its mechanisms at the cellular and molecular level are not well understood. Results We investigated the effect of propolis on antiviral signaling in A549 cells transfected with double‐stranded RNA (dsRNA), a model for viral infection. Pretreatment of the cells with propolis inhibited poly I:C (synthetic dsRNA)‐induced interferon (IFN)‐β expression. Propolis had no effect on the dsRNA‐induced expression of RIG‐I‐like receptors (RLRs), which are known as intracellular viral RNA sensors. As to the effect on antiviral executor genes, propolis enhanced myxovirus resistance 1 (MX1) expression, whereas interferon‐inducible gene 6–16 (G1P3) and 2'‐5'‐oligoadenylate synthetase (OAS) were unaffected. All of these genes belong to the IFN‐inducible genes, suggesting that the effect of propolis on antiviral signaling is not necessarily mediated by the autocrine regulation by IFN‐β. Propolis pretreatment inhibited dsRNA‐induced interleukin‐8 (IL8) and CCL5 expression, and consequently lowered polymorphonuclear leukocyte (PMN) chemotactic activity in the cell‐conditioned medium. Conclusion Taken together, these results suggest that propolis may suppress excess inflammatory responses without affecting the innate immunity during viral infection.